Discovery of novel 3-butyl-6-benzyloxyphthalide Mannich base derivatives as multifunctional agents against Alzheimer's disease. (15th March 2022) - Liu, Zhuoling; Shi, Yichun; Zhang, Xiaoyu; Yu, Guangjun; Li, Jingjing; Cong, Shiqin; Deng, Yong
Graphical abstract: Highlights: Novel 3-butyl-6-benzyloxyphthalide Mannich base derivatives were synthesized. Most compounds showed good AChE, MAO-B inhibitory activities. Compound 7d can effectively alleviate oxidative stress and neuroinflammatory damage. 7d was the outstanding representative with good multifunctional and drug-like properties. Abstract: Based on the multitarget-directed ligands strategy, a series of 3-butyl-6-benzyloxyphthalide Mannich base derivatives were designed, synthesized and identified for Alzheimer's disease (AD). Biological activity studies demonstrated that the designed hybrids showed multitarget activities toward AD. Among them, compound 7d was the most potent agent with excellent inhibitory activities on Ee AChE (IC50 = 0.087 μM), Hu AChE (IC50 = 0.041 μM) and MAO-B (IC50 = 0.30 μM). Furthermore, molecular docking studies were conducted to investigate the interaction mode with enzymes. Besides, 7d also possessed good effects of Cu 2+ chelation, ameliorate oxidative stress, and anti-neuroinflammation, desirable BBB permeability and eligible drug-like properties. Altogether, the multifunctional profiles of 7d prove that it deserves further investigation as a novel drug candidate for AD treatment.